Managing voluntary and non-profit organizations : strategy and structure - Butler, Richard J., 1938-; Wilson, David C. (David Charles), 1951- (London ; New York : Routledge, Taylor & Francis Group, 2015)
Drawing on detailed empirical data and a range of case studies, Managing Voluntary and Non-Profit Organizations, first published in 1990, demonstrates how voluntary organizations formulate strategies for securing funds, providing services, and dealing with other non-profit bodies, public agencies, and the private sector. The central theme is organizational change and how managers have responded, strategically and structurally, to changes to their environment. Using original data, and writing from the broad perspectives of current organization theory, the authors increase our understanding of strategies, structures and designs currently in use in the voluntary sector. Their authoritative text will make essential reading for practising managers in non-profit organizations and for an international audience of academics and students of management, organization theory, and strategy.
Publikace se zabývá řízením dobrovolných a neziskových organizací se zaměřením na strategii, organizační strukturu a procesy změny. Na základě empirických dat a případových studií analyzuje, jak se neziskové organizace přizpůsobují proměnám svého vnějšího prostředí, získávání zdrojů a spolupráci s veřejným i soukromým sektorem. Kniha je určena manažerům neziskových organizací i studentům a badatelům v oblasti managementu a teorie organizace.
Obsahuje bibliografické odkazy a rejstříky
Keywords: neziskové organizace; strategický management; organizační změna; případové studie; dobrovolnické organizace; monografie; nonprofit organizations; strategic planning; organizational change; case studies; monographs